If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 9) = 48 Reorder the terms: 3(9 + x) = 48 (9 * 3 + x * 3) = 48 (27 + 3x) = 48 Solving 27 + 3x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 3x = 48 + -27 Combine like terms: 27 + -27 = 0 0 + 3x = 48 + -27 3x = 48 + -27 Combine like terms: 48 + -27 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| -113=5x+-2(7x+25) | | 1s+-3=-6 | | (1/2)x+16=(2/3)x-4 | | 450=1200-3t | | x*2-12=44 | | 4ab-3ab^2= | | 45x=1548 | | 2x+15=5x-30 | | 7x=3y-12 | | 32x^2+16x-6=0 | | 9.4-0.7h+2.6-1.3d=5-2.0d-6.2 | | 0=(x^2)-5x+1 | | 256=6x+-4(-4x+-20) | | 4m-6=6(m+2)+8 | | (2x+4)(x-8)=0 | | -2(7x+1)=14x | | 6r+22=4(4+3r) | | 3-x=-497 | | -2(x+1)+1=20 | | 1x+4=9 | | 24=7x+-4(2x+-4) | | -0.16=3.7 | | -0.13x=3.9 | | 2(x+3)+5x=15-(2x+18) | | 60-4x=4x^2 | | y^2-3y-5=0 | | 4x+36=108 | | 9y+5=5*(y+5) | | 3x^2+49x=0 | | -14=-4[9x-1] | | 9(7-2-3-(9-8))=0 | | 0.5x+17+x=20 |